Kajian Faktor-Faktor Penyebab Contract Change Order (CCO) Pada Proyek Konstruksi di Kota Palangka Raya - Salwa Inka Yunisa; Veronika Happy Puspasari (Jurnal Basement : Jurnal Teknik Sipil, 2024)
A construction project is a series of activities carried out only once and generally within a short period of time. Construction projects are related to the construction of a building, which then functions in various activities related to the government and the private sector. In the project implementation process, obstacles often occur such as changes. These changes can occur at the beginning, middle and end of the project. The problem that is often experienced in construction work is changes, where the changes themselves can be in the form of differences in volume, additions or reductions in work, with these changes it cannot be denied that there will be a change to the work contract or Contract Change Order. Project administration must be carried out carefully and structured correctly to avoid errors that can have an impact on all sectors. This research uses descriptive research where researchers will analyze data from survey results by distributing questionnaires to respondents with the aim of finding out the Contract Change Order factors that occur in Palangka Raya City. The method used is a literature study on Contract Change Orders by comparing related journals. The results obtained are that there are 4 Contract Change Order Factors, namely Planning and Design, Administration, Construction and Stakeholders which have 20 sub-factors Contract Change Order